Factors associated with PrEP adherence among MSM living in Jackson, Mississippi. Issue 3 (3rd July 2021) - Whiteley, Laura; Craker, Lacey; Sun, Shufang; Tarantino, Nicholas; Hershkowitz, Dylan; Moskowitz, Jesse; Arnold, Trisha; Haubrick, Kayla; Olsen, Elizabeth; Mena, Leandro; Brown, Larry K.
Abstract: Understanding the determinants of pre-exposure prophylaxis (PrEP) adherence is integral to reducing HIV incidence in the United States, especially for those at highest risk. To this end, the present study explored demographic, psychosocial, and behavioral factors related to adherence among 43 Southern, predominately Black, men who have sex with men (MSM). During the study months, 46% of the sample reported being nonadherent to PrEP. Those with more sexual partners ( p  = .05), greater self-efficacy for taking PrEP ( p  = .03), and those who felt condoms were less important ( p  = .02), were more likely to be adherent to PrEP at six-month follow-up. Further interventions that consider perceived sexual risk, condom use, and adherence self-efficacy are needed to improve PrEP adherence among Southern MSM.